A review of occupationally–relevant models of localised muscle fatigue. (19th March 2015) - Rashedi, Ehsan; Nussbaum, Maury A.
Localised muscle fatigue (LMF) is a complex phenomenon that can differ between individuals, tasks, and muscles. Several muscle fatigue models (MFMs) have been developed in prior research. MFMs have potential practical value in ergonomics, given that LMF can impair performance, serve as a surrogate measure of injury risk, and may act as a causal factor for work–related musculoskeletal disorders. Existing MFMs are reviewed here, and which are broadly classified as either 'empirical' or 'theoretical'. Two specific MFMs, considered most ergonomically–relevant, were directly compared and some important differences in predictions were found. Identifying such differences is suggested as a useful approach, both for developing testable hypotheses and in guiding subsequent model development or refinement. Other potential approaches for improving future MFMs are also discussed, including expansion of model structure to account for individual differences (e.g., age, gender, and obesity), task related parameters, and variability in motor unit composition.